Preventive effect of tacrolimus on patients with post-endoscopic retrograde cholangiopancreatography pancreatitis - Harshavardhan Rao B.; Paul K. Vincent; Priya Nair; Anoop K. Koshy; Rama P. Venu (Korean Society of Gastrointestinal Endoscopy, 2022)
Background/Aims In patients undergoing endoscopic retrograde cholangiopancreatography (ERCP), calcineurin activates zymogen, which results in pancreatitis. In this study, we aimed to determine the efficacy of tacrolimus, a calcineurin inhibitor, in preventing post-ERCP pancreatitis (PEP). Methods This was a prospective pilot study in which patients who underwent ERCP received tacrolimus (4 mg in two divided doses); this was the Tac group. A contemporaneous cohort of patients was included as a control group. All patients were followed-up for PEP. PEP was characterized by worsening abdominal pain with an acute onset, elevated pancreatic enzymes, and a duration of hospital stay of more than 48 hours. Serum tacrolimus levels were measured immediately before the procedure in the Tac group. Results There were no differences in the baseline characteristics between the Tac group (n=48) and the control group (n=51). Only four out of 48 patients (8.3%) had PEP in the Tac group compared to eight out of 51 patients (15.7%) who had PEP in the control group. The mean trough tacrolimus level in patients who developed PEP was significantly lower (p<0.05). Conclusions Oral tacrolimus at a cumulative dose of 4 mg safely prevents PEP. Further randomized controlled studies are warranted to establish the role of tacrolimus in this context.